THE ROLE OF MADRASAH‘S OF THE GREAT SELJUK PERIOD (1038-1157) IN THE DEVELOPMENT OF ISLAMIC CIVILIZATION - Rajapov Pirnazar Sardor ogli (Journals Park Publishing, 2024)
This article analyzes the reforms which carried out in the field of study in the Great Seljuk Sultanate and the reasons for them. Besides, the process of establishing madrasah‘s in Khorasan, Kerman, Iraq, Syria, and Anatolia regions of the country and the goals of the establishment of madrasah‘s have been revealed. The role of these madrasah‘s in the development of Islamic civilization is also discussed.
Keywords: The Great Seljuk Sultanate, the Fatimids, madrasah, Al-Azhar madrasah, Sultan Alp Arslan, Sultan Malik-Shah, Sultan Sanjar, Nizamiya madrasah of Baghdad, mudarris, muid.